Proceedings of the Eleventh Leadership Seminar, 19-20th May, Hotel Istana, Kuala Lumpur - Leadership Seminar (SEACEUM) (11th : 2004 : Kuala Lumpur); Universiti Teknologi Malaysia. Institut Sultan Iskandar; Yayasan Hanns Seidel, Germany (Skudai : Institute Sultan Iskandar, 2004)
28